1963
DOI: 10.1017/s0003356100021486
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of a crop husbandry technique in terms of animal production

Abstract: SUMMARY1. The energy value of three hays cut at three stages of maturity was. measured by calorimetric methods and, in addition, the amounts of the hays consumed voluntarily by sheep were measured. Voluntary intake was alsa measured when 200, 500, 800 and 1,200 g. of pelleted concentrates were given.2. The metabolisable energy values of the three hays measured at the-maintenance level were 2·45, 2·26 and 2·16 kcal./g. for cuts 1, 2 and 3-respectively (cut 1 being the earliest). The net energy values for fat pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
37
7

Year Published

1964
1964
1989
1989

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 5 publications
8
37
7
Order By: Relevance
“…These results concur with those of Blaxter and Wilson (1963), Murdoch (1964) and Crabtree and Williams (1971) in showing that the voluntary intake of hay in hay-concentrate diets is a function of hay quality, proportion of concentrate in the diet and concentrate protein level. Donefer et al (1963) found that when lambs were given ground, pelleted diets compounded from varying proportions of barley and lucerne, the voluntary intake of the total diet declined as the percentage of barley increased, but digestible energy intake remained approximately constant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results concur with those of Blaxter and Wilson (1963), Murdoch (1964) and Crabtree and Williams (1971) in showing that the voluntary intake of hay in hay-concentrate diets is a function of hay quality, proportion of concentrate in the diet and concentrate protein level. Donefer et al (1963) found that when lambs were given ground, pelleted diets compounded from varying proportions of barley and lucerne, the voluntary intake of the total diet declined as the percentage of barley increased, but digestible energy intake remained approximately constant.…”
Section: Discussionsupporting
confidence: 89%
“…However, at the higher levels of barley feeding (B^.Bi) the substitution rates observed were of the same order as those recorded by the other workers. The differences between results in the hay intake response to barley feeding when soya bean meal was not given may be related to differences in the quality of the hays used (Blaxter and Wilson, 1963). The digestibility and crude protein content of the hays used by the other workers were higher than for the hay used in the present study.…”
Section: Discussioncontrasting
confidence: 59%
“…That level of protein in the diet, below approximately 10 % crude protein, affects voluntary intake of food by ruminants is now well established (Campling et al 1961Blaxter & Wilson, 1963;Elliott & Topps, 1963c)). Confirmation of this finding was obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Developmen s in additive technology indicate a potential for formic acid/formaldehyde mixtures since formaldehyde has been shown not only to reduce fermentation (Wilkins, Wilson and Woolford, 1974) but also to tPresent address: Agricultural Research Council, 160 Great Portland Street, London WIN 6DT. increase the supply of amino acids from silage to the animal (Beever, Thomson, Cammell and " • 10771 Differences in voluntary intake and animal performance, apparent when forages are given as the sole feed, are much reduced in the presence of a supplement (Blaxter and Wilson, 1963 …”
Section: Introductionmentioning
confidence: 99%